Parental Partnership in Implementing the Hajj Manasik Activity Program at RA Raudhatul Faizin - Ritonga, Julianti; Hidayatun, Nur; Wulandari, Susi; Sit, Masganti (International Journal of Education, Information Technology, and Others, 2024)
Hajj simulation (manasik haji) for early childhood is a simplified learning activity designed to introduce children to the rituals of Hajj while teaching religious values such as piety, cooperation, and independence. This partnership is a collaborative effort involving parents in various educational activities, both at school and at home. This study aims to explore the role of parents in supporting the implementation of Hajj simulation activities at RA Raudhatul Faizin. Using a qualitative approach, data were collected through observation, interviews, and documents. The findings show that parents who were actively involved in preparation, implementation, and evaluation of the activities helped children to understand and enjoy the experience. However, there were challenges such as time constraints and limited understanding among some parents. This study recommends the need for better communication and training for parents to ensure that these activities run more smoothly in the future.